1995
DOI: 10.1159/000113561
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Central Biogenic Amines Following Aggressive Interaction in Male Lizards, <i>Anolis carolinensis</i>

Abstract: Many stimuli, including social aggression, activate endocrine stress mechanisms, presumably mediated or modulated by central neurotransmitters. To determine the effects of aggression on central neurochemistry, reproductively active male Anolis carolinensis were paired and allowed to establish social dominance relationships. While combatants cohabited, the fight losers invariably became socially subordinate and displayed darker color, selection of lower perch sites, and lower body posture than the winners. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 13 publications
4
42
0
1
Order By: Relevance
“…In several species in which the serotonergic system has been analyzed during agonistic interactions, serotonergic activity increases consistently in subordinates (Yodyingyuad et al, 1985;Blanchard et al, 1991;Summers and Greenberg, 1995;Overli et al, 1999;Summers et al, 2005b) and decreases or remains unchanged in dominants (van Erp and Miczek, 2000;Ferrari et al, 2003;Summers et al, 2003). The activation of 5-HT 1A receptors has been involved in the inhibitory effect of 5-HT on aggression in all vertebrate classes (Deckel and Fuqua, 1998;Sperry et al, 2003;Miczek and Fish, 2006;Clotfelter et al, 2007;Allee et al, 2008;Ten Eyck, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In several species in which the serotonergic system has been analyzed during agonistic interactions, serotonergic activity increases consistently in subordinates (Yodyingyuad et al, 1985;Blanchard et al, 1991;Summers and Greenberg, 1995;Overli et al, 1999;Summers et al, 2005b) and decreases or remains unchanged in dominants (van Erp and Miczek, 2000;Ferrari et al, 2003;Summers et al, 2003). The activation of 5-HT 1A receptors has been involved in the inhibitory effect of 5-HT on aggression in all vertebrate classes (Deckel and Fuqua, 1998;Sperry et al, 2003;Miczek and Fish, 2006;Clotfelter et al, 2007;Allee et al, 2008;Ten Eyck, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Increased 5-hydroxyindoleacetic acid (5-HIAA), indicative of serotonin (5-HT) catabolism, is associated with subordinate social roles in vertebrates as taxonomically diverse as fishes [Winberg et al, 1992a; and primates [Yodyingyuad et al, 1985]. Increased serotonergic activity is coincident with subordinate behavior, such as decreased feeding rates and locomotor activity and increased receipt of aggressive attacks in salmonid fish [Winberg et al, 1992b], reptiles [Summers and Greenberg, 1995] and mammals [Yodyingyuad et al, 1985]. Staged agonistic encounters between pairs of lizards, Anolis carolinensis, lead to significant increases in serotonin turnover in subordinates (losers), lasting for up to a day, compared to winners (dominant) and isolated controls [Summers and Greenberg, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Increased serotonergic activity is coincident with subordinate behavior, such as decreased feeding rates and locomotor activity and increased receipt of aggressive attacks in salmonid fish [Winberg et al, 1992b], reptiles [Summers and Greenberg, 1995] and mammals [Yodyingyuad et al, 1985]. Staged agonistic encounters between pairs of lizards, Anolis carolinensis, lead to significant increases in serotonin turnover in subordinates (losers), lasting for up to a day, compared to winners (dominant) and isolated controls [Summers and Greenberg, 1995]. In addition, activation of catecholaminergic systems appears to be associated with increased levels of aggression [Eichelman, 1987;Zebrowska-Lupina et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the memory of opponents and their status is more important for determining subsequent social behavior and rank than the social sign stimuli presented by the eyespots. We also believe that firmly established of rank relationships, not greatly affected by eyespot color change, nor aggressively disputed, constrained stimulation of serotonergic activity that is usually evident following social antagonism in specific regions of the aggression neurocircuitry [35,37,39,49,68,70,72,73,[75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 88%
“…Unlike previous studies that have repeatedly demonstrated specifically activated serotonergic systems in centers of aggression neurocircuitry, in the study reported here we measured no change in any serotonergic parameter nucleus accumbens, medial amygdala, lateral amygdala or anterior hypothalamus. These regions particularly, but also other regions, have been demonstrated to rapidly, or for some regions more slowly, increase serotonergic output and/or metabolism [35,37,39,49,68,70,72,73,[75][76][77][78][79]. Aggressive social interactions that determine social status produce different hormonal and central neurochemical patterns, particularly of serotonergic and dopaminergic activity, dependent on status of each individual [33,35,40,[68][69][70]73,[75][76][77][78].…”
Section: Central Monoaminergic Response To a Second Social Interactionmentioning
confidence: 99%